Entre sinos e drive-thrus no reino de Deus : tramas tecnoestéticas e atmosferas sensoriais - Chagas, Andréa Basílio da Silva (2013)
In this work we aim to study the tecnoestética the Universal do Reino de Deus Church (IURD), more precisely study the light of Simondon creating atmospheres sensory iurdianas and its contribution to the study of aesthetic dimensions of the techniques. In our observations, we find a set of artefatualidades that made us "boarding" in this quest for understanding the networks of materiality iurdianas. As these artifacts construct church environments, as performam and affect religious experience in contemporary times. For this work, were made: observations ethnographic and interviews, most of the work was done in IURD Cuiabá, however, due to complications from the field, our research has extended to three capitals: Brasília, São Paulo and Rio de January. Our thesis was built in five chapters, all grounded in the thinking of our top authors: Simondon, with studies of tecnoestética, and Bruno Latour, basing questions about religion, communication and network theory.